Penggunaan Etnomatematika Guna Meningkatkan Pemahaman Konsep Siswa - Nusantari, Diah Oga; Zulkarnain, Ihwan; Nurhayati (CV Buana Prisma Sejahtera, 2024)
Innovation in the approach to learning mathematics is very necessary. The approach will be more easily accepted if it is related to the daily life of our culture. Ethnomathematics is a science used to understand how mathematics is adapted from a culture and functions to express the relationship between culture and mathematics. The purpose of this community service activity is to introduce the Ethnomathematics approach to mathematics subjects so that it is expected to improve students' understanding of mathematical concepts. The activity was held at SMK YAPPA Depok, West Java. Community service activities involved students and lecturers of the Mathematics Education Study Program. Mathematics education students as prospective mathematics teachers must be able to find solutions to students' difficulties in understanding mathematical concepts. One way is to apply the Ethnomathematics course obtained in lectures. The approach using Ethnomathematics is expected to be a solution to the problems that occur in students at school